الإنجازات والتقييم لوزارة شؤون الشمال العراقية 1967-1978 - الدليمي، حسن ضاري سبع; مظلوم، حسن ناصر (جامعة الكوفة - مركز دراسات الكوفة, 2024)
تناول هذا البحث الإنجازات التي قامت بها وزارة شؤون الشمال العراقية عندما أصبح لها وضع مستقل وميزانية مالية خاصة بها، فعملت من هذا المنطلق وبوتيرة عالية في تقديم ما تستطيع تقديمة من خدمات في كافة القطاعات الخدمية وهذا جاء بالتعاون مع بقية الوزارات الساندة لها مثل وزاراتي الصحة والتربية، على الرغم من تجاهل الحكومات لهذه الوزارة في بعض الأوقات لتباين في الأفكار من كانوا على سدة الحكم، ثم تطرق البحث إلى تقييم هذه الوزارة من حيث أدائها والقوانين التي صدرت بحقها من اجل تسيير أعمالها. This research dealt with the achievements made by the Iraqi Ministry of Northern Affairs when it had an independent status and a financial budget of its own, so it worked from this point of view and at a high pace in providing what services it could provide in all service sectors, and this came in cooperation with the rest of the ministries supporting it, such as the two ministries of health And education, despite governments ignoring this ministry at times due to the discrepancy in the ideas of Issue 72, Part 1, March 2024 PAGE 386 those who were in power, then the research touched on the evaluation of this ministry in terms of its performance and the laws issued against it in order to run its work.
Keywords: الثروات الطبيعية -- المشاريع الصناعية -- القدرات المؤسسية -- التنمية الدولية